Functional Coordination among the Golgi Complex, the Centrosome and the Microtubule Cytoskeleton during the Cell Cycle - Fabiola Mascanzoni; Roberta Iannitti; Antonino Colanzi (Cells, 2022)
The Golgi complex of mammalian cells is organized in a ribbon-like structure often closely associated with the centrosome during interphase. Conversely, the Golgi complex assumes a fragmented and dispersed configuration away from the centrosome during mitosis. The structure of the Golgi complex and the relative position to the centrosome are dynamically regulated by microtubules. Many pieces of evidence reveal that this microtubule-mediated dynamic association between the Golgi complex and centrosome is of functional significance in cell polarization and division. Here, we summarize findings indicating how the Golgi complex and the centrosome cooperate in organizing the microtubule network for the directional protein transport and centrosome positioning required for cell polarization and regulating fundamental cell division processes.